2021
DOI: 10.1038/s41398-021-01583-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased activation product of complement 4 protein in plasma of individuals with schizophrenia

Abstract: Structural variation in the complement 4 gene (C4) confers genetic risk for schizophrenia. The variation includes numbers of the increased C4A copy number, which predicts increased C4A mRNA expression. C4-anaphylatoxin (C4-ana) is a C4 protein fragment released upon C4 protein activation that has the potential to change the blood–brain barrier (BBB). We hypothesized that elevated plasma levels of C4-ana occur in individuals with schizophrenia (iSCZ). Blood was collected from 15 iSCZ with illness duration < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…2 ), whereas no association was found with CSMD1 mRNA levels ( β = − 0.03; p = 0.817), as expected. In agreement with recent evidence from an independent FEP study [ 22 ], we observed that the AL-BL haplotype group was the most common among FEP cases (56%), compared to a much lower frequency reported within healthy individuals (41%) in the original study by Sekar et al . (2016).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…2 ), whereas no association was found with CSMD1 mRNA levels ( β = − 0.03; p = 0.817), as expected. In agreement with recent evidence from an independent FEP study [ 22 ], we observed that the AL-BL haplotype group was the most common among FEP cases (56%), compared to a much lower frequency reported within healthy individuals (41%) in the original study by Sekar et al . (2016).…”
Section: Resultssupporting
confidence: 93%
“…Moreover, we acknowledge as an additional limiting factor the slightly smaller number of FEP cases included in the C4A protein assays that might have reduced the statistical power of the analysis. Likewise, C4 haplogroup analysis among FEP cases did not reveal an association between C4A copy number status and C4A protein levels in serum, as opposed to an earlier study which examined a limited number of plasma samples from medicated SZ patients [ 22 ].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, it remains to be seen whether the existing references and level of interest are sufficient to generate more evidence and obtain approval of those substances for the treatment of schizophrenia. Furthermore, following the increasing recognition of the significant role of inflammation and immunological dysregulation in the development of schizophrenia, a growing number of compounds are also being explored in this area [306][307][308][309][310][311], although these approaches are currently at early stages of development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, subclinical inflammation seems to correlate with higher levels of cognitive impairment, underlining the possible utility of anti-inflammatory agents [306][307][308]. Additionally, based on genetic, transcriptomic, and functional studies, dysregulation in the complement system, which mediates innate immunity, has been reported in patients with schizophrenia [309].…”
Section: Anti-inflammatory and Immunomodulatory Approachesmentioning
confidence: 99%